The Use of Clustering Technique for Improving Writing Description Text of the Third Semester Students Of Unindra - Widyawati, Wiwik Yully (Universitas Muria Kudus, 2018)
The purpose of the study is To find out the clustering technique is effective or not in improving students’ ability in generating ideas for writing description text of the third semester of the English Department of UNINDRA in the academic year of 2017/2018”. Target in this research is scholar of university. The sample of this research is thirty students. This research uses book and test as the source of data. In this case, test used in this research is writing test about writing description text. This research uses a quantitative method, experiment. The findings of this research are by analyzing the students’ test about writing description text. After analyzing data, the result of the test applied to the students by using clustering technique showed that the highest score was 88, the lowest was 65. The mean score was 78.3. If it is consulted to the grade classification of writing, the mean achievement belongs to good grade, while for control group or by using conventional technique, the highest score was 70 and the lowest score was 35. The mean score was 52.8. If it is consulted to the grade classification of writing, the mean achievement belongs to poor grade. Based on the statement above, it can be concluded that the result of research said that there is good effect clustering technique in improving the third students’ ability in writing description text. So, the technique clustering is effective for improving writing ability.keywords: technique of learning, clustering technique, writing skill and descriptive texts.